Review of the Arabic Language Curriculum at Al Mawaddah Ciganjur Islamic Senior High School - Muhammad Latif; Eva Siti Faridah; Adrian Ariel Pamungkas; Muhammad Ilham Prakoso (Aslim: Journal of Education and Islamic Studies, 2024)
The curriculum continuously evolves over time, often aligning with the prevailing government policies. Currently, the Merdeka Curriculum has been introduced as the latest educational framework. This study aims to examine the Arabic language curriculum at Madrasah Aliyah Al-Mawaddah Ciganjur and evaluate the implementation of the Merdeka Curriculum in Arabic language learning at the institution. A descriptive qualitative approach was employed, with data collection methods including observation, documentation, and document analysis. Data analysis followed an interactive model consisting of data collection, data presentation, data reduction, and conclusion drawing. The findings reveal that students' ability to respond to questions regarding interrogative sentences in Arabic varies significantly. Some students possess prior learning experiences in Islamic boarding schools (pesantren) and a basic understanding of Arabic, while others lack such backgrounds. The syllabus incorporates active discussion sessions between teachers and students, ensuring that the learning process is not solely dependent on written materials. Learning evaluations include text analysis tasks focusing on interrogative sentences in Arabic. However, the implementation of the Merdeka Curriculum at Madrasah Aliyah Al-Mawaddah Ciganjur faces several challenges, particularly in teacher competency, availability of teaching materials, teaching methods, and learning media.